A six-month epidemiologic study of carbapenem-resistant Acinetobacter baumannii and carbapenem-resistant Pseudomonas aeruginosa in early pandemic at Dr. Soetomo Hospital Surabaya - Pristiawan Navy Endraputra; Kuntaman; Eko Budi Khoendori (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2021)
Background: Nosocomial infection is derived from the patient itself or transmitted across patients, healthcare workers, or the hospital environment. Carbapenem-resistant Acinetobacter baumannii (CRAB) and Pseudomonas aeruginosa (CRPA) have been recognized as the most common pathogen for nosocomial infections in Southeast Asia. Afterward, CRAB and CRPA infections increase morbidity, mortality, length of stay, and cost. This study examined the prevalence of CRAB and CRPA at Dr. Soetomo Hospital, Surabaya, from January to June 2020. Methods: This descriptive study was conducted retrospectively by collecting data from the first isolate per specimen per patient of Acinetobacter baumannii and Pseudomonas aeruginosa, resistant either to meropenem or imipenem from urine, blood, pus, or sputum in Dr. Soetomo Hospital, Surabaya within January to June 2020. Results: A total of 311 Acinetobacter baumannii and 425 Pseudomonas aeruginosa were collected with 134 CRAB and 79 CRPA. The resistance rate of CRAB was ≥90% except for amikacin, cefoperazone-sulbactam, levofloxacin, tigecycline, trimethoprim-sulfamethoxazole, and fosfomycin. Moreover, CRPA had resistance ≥90% regardless of intrinsic resistance against imipenem and colistin. There was an increase in CRAB and CRPA, with the highest incidence in June 2020 in early 2020. Conclusion: The prevalence of CRAB and CRPA were 43% and 19%, respectively, in the early six months of 2020 at Dr. Soetomo Hospital, Surabaya.